Opinions of Student Nurses Practicing Clinical Practice in a University Hospital - Şehrinaz Polat; Habibe Ayyıldız Erkan; Güldalı Çınar; Leyla Afşar Doğrusöz (Association of Nurse Managers, 2018)
INTRODUCTION: The purpose of this study was to determine the nurses 'and clinic nurses' clinical experience in the institution and to determine the causes of these problems and to plan the necessary actions for corrective measures. METHODS: METHODS: A questionnaire was applied to nursing undergraduate students who applied in a university hospital during the summer term between 2011, 2012 and 2013. The sample of the research consists of 657 students. T-test in independent groups, Kruskal-Wallis one way ANOVA and Mann Whitney U test was used in the study. The significance limit was p <0.05 and bi-directional. RESULTS: RESULTS: 37.9% of the students were practiced in 2012 and 54% of them were practicing in surgical clinics. "The work intensity of nurses is decreasing due to the students during internship days of student nurses" has the highest average (4,15+-0,95). The lowest mean is "The presence of the students restricts the time of nurses allocate to the patient" in the clinic (1,72+-1,06). DISCUSSION AND CONCLUSION: ADISCUSSION AND CONCLUSION: According to the answers given by the students, it is necessary that the students who come to apply are informed about the other employees about the students, more clinical presentation and guidance are needed.